Get the picture: Central Australian indigenous paintings, which reveal collaborative thought about contemporary social situations - C. San Roque (Law Text Culture, 2006)
In central Australian languages the words for ‘thinking’ and ‘understanding’ are the words for ‘listening’ and ‘hearing’. The root verb, kulini (Pitjantjatjatjara) leads to kulinara palyani; ‘to plan or work out how to do something’. This is what we are doing here; looking at these paintings; trying to ‘get the picture’ and attending to what the pictures reveal.